Land‐Atmosphere Coupling Constrains Increases to Potential Evaporation in a Warming Climate: Implications at Local and Global Scales - Yeonuk Kim; Monica Garcia; Mark S. Johnson (Earth's Future, 2023)
Abstract The magnitude and extent of runoff reduction, drought intensification, and dryland expansion under climate change are unclear and contentious. A primary reason is disagreement between global circulation models and current potential evaporation (PE) models for the upper limit of evaporation under warming climatic conditions. An emerging body of research suggests that current PE models including Penman‐Monteith and Priestley‐Taylor may overestimate future evaporation for non‐water‐stressed conditions. However, they are still widely used for climatic impact analysis although the underlying physical mechanisms for PE projections remain unclear. Here, we show that current PE models diverge from observed non‐water‐stressed evaporation across site (>1,500 flux tower site years), watershed (>10,000 watershed‐years), and global (25 climate models) scales. By not incorporating land‐atmosphere coupling processes, current models overestimate non‐water‐stressed evaporation and its driving factors for warmer and drier conditions. To resolve this, we introduce a land‐atmosphere coupled PE model by extending the Surface Flux Equilibrium theory. The proposed PE model accurately reproduces non‐water‐stressed evaporation across spatiotemporal scales. We find that terrestrial PE will increase at a similar rate to ocean evaporation but much slower than rates suggested by current PE models. This finding suggests that land‐atmosphere coupling moderates continental drying trends. Budyko‐based runoff projections incorporating our PE model are well aligned with those from coupled climate simulations, implying that land‐atmosphere coupling is key to improving predictions of climatic impacts on water resources. Our approach provides a simple and robust way to incorporate coupled land‐atmosphere processes into water management tools.